PTFE catalytic filter material and preparation method thereof
By using multiple impregnation processes of catalyst dispersion and PTFE needle felt in the preparation of PTFE catalytic filter material, the problems of complex preparation process, large catalyst usage and poor catalytic effect in the prior art are solved, and uniform adhesion and efficient catalytic performance of the catalyst are achieved, cost is reduced and controllability of the preparation is improved.
Patent Information
- Application Number
- CN202310203122.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-03
AI Technical Summary
The existing PTFE catalytic filter material preparation process is complex, the catalyst usage is large, the catalytic effect is poor, and the dispersion of the catalyst is poor, resulting in a degradation of catalytic denitrification performance.
The dispersion is formed by mixing the catalyst with a solvent, and the PTFE needle felt is impregnated multiple times in the catalyst dispersion. The emulsification of the surfactant is used to uniformly disperse the nano-scale PTFE particles on the surface of the filter material, thereby improving the catalyst adhesion firmness and catalytic effect.
The uniform adhesion and efficient dispersion of the catalyst on the PTFE needle felt are achieved, the catalytic performance of the catalyst is improved, the device cost is reduced, and the amount of catalyst adhesion can be controlled by regulating the number of impregnation times, thereby achieving a controllable loading of catalytic filter material preparation.
Smart Images

Figure CN116139595B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial flue gas dust removal, and in particular to a PTFE catalytic filter material and a preparation method thereof. Background Art
[0002] PTFE filter bags have the characteristics of acid and alkali resistance, water resistance, anti-caking and long service life, and have a wide range of application markets in the field of industrial flue gas dust removal. At present, the removal of dust and nitrogen oxide pollutants in industrial flue gas is carried out separately by using two sets of devices, filter bag dust removal and selective catalytic reduction (SCR). There are disadvantages such as high device cost, high operation and maintenance costs, and large floor space. The use of the same product to achieve the coordinated treatment of multiple pollutants is the development trend of industrial flue gas treatment in the future. Due to the inertness of the surface of PTFE material, it is challenging to achieve catalyst loading. At present, the technology mostly uses PTFE dispersed resin and catalyst powder to mix, press rods, extrude wires, calender film, and needle punch to make PTFE filter materials containing catalysts. This technology requires the technology and process of filter bag production. The dispersion of the catalyst in the obtained catalytic filter material is poor, and most of it exists inside the PTFE fiber. The encapsulated catalyst loses its catalytic activity. This method will not only cause a large amount of waste of catalyst raw materials, but also greatly reduce the performance of catalytic denitrification, which is not conducive to the promotion and use of this technology.
[0003] The preparation technology of PTFE catalytic filter materials reported at this stage mainly focuses on mixing polytetrafluoroethylene resin (PTFE for short) and catalyst powder to form a catalytic filter bag. It has the following defects: ① This method requires filter bag manufacturing technology and process conditions, and the process is complicated; ② The polytetrafluoroethylene resin and catalyst powder are not mixed evenly, resulting in poor dispersion of the catalyst; ③ The polytetrafluoroethylene fiber formed by drawing will wrap the catalyst powder inside, making the catalyst unable to contact with the reaction gas and lose its catalytic effect. Summary of the invention
[0004] The main purpose of the present invention is to provide a PTFE catalytic filter material and a preparation method thereof, so as to solve the problems of complex preparation process of PTFE catalytic filter material, large amount of catalyst and poor catalytic effect in the prior art.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a PTFE catalytic filter material is provided, and the preparation method comprises: step S1, mixing a catalyst with a solvent to obtain a catalyst dispersion; step S2, performing a first impregnation of the PTFE needle felt in the catalyst dispersion to obtain a first impregnated filter material; step S3, performing a second impregnation of the first impregnated filter material in the impregnation liquid to obtain a PTFE catalytic filter material, wherein the impregnation liquid comprises nano-scale PTFE particles and a surfactant, and the particle size of the catalyst is nano-scale.
[0006] Furthermore, the preparation method also includes: calcining the filter material after the second impregnation to obtain a PTFE catalytic filter material, wherein the PTFE needle-punched felt is a flat strip fiber, the flat strip fiber preferably has a fiber fineness of 2 to 10 dtex, the particle size of the nanoscale PTFE particles is preferably 150 to 170 nm, the calcination temperature is preferably 250 to 270°C, and the calcination time is preferably 1 h to 2 h.
[0007] Furthermore, in the above step S1, the mixing process includes: stirring the catalyst and the solvent and then ultrasonicating them, preferably the stirring speed is 400-800r / min, and the stirring time is preferably 5-10 minutes; the ultrasonic frequency is preferably 28000-40000Hz, and the ultrasonic time is preferably 10-20 minutes. The volume ratio of the catalyst to the solvent is preferably 1:5-15, and the particle size of the catalyst is preferably 30-58nm. The catalyst is preferably selected from 3wt%V2O5-10wt%MoO3 / Any one or more of TiO2 catalyst, 3wt% V2O5-10wt% MoO3-xwt% CeO2 / TiO2, 3wt% V2O5-10wt% WO3 / TiO2, wherein x ranges from 1 to 10, and the mass percentage of each component in the catalyst is relative to the mass of TiO2 in the catalyst as 100%; the preferred solvent is selected from any one or more of ethanol, propanol, acetone, and a mixed solution of ethanol and water, wherein the water content in the mixed solution is ≤13%.
[0008] Further, in the above step S3, the first impregnation is repeated for multiple times, and preferably the process of each second impregnation includes: after the front side of the first impregnated filter material is impregnated for 5 to 10 minutes, the first impregnated filter material is turned over and then impregnated for 5 to 10 minutes; preferably, the first impregnation is repeated 2 to 3 times, preferably, in terms of mass percentage, the impregnation liquid includes: 0.3 to 12 wt% of PTFE particles; 0.05 to 1.5 wt% of a surfactant; 0.1 to 5 wt% of a foaming agent; and 83 to 99.6 wt% of water, and preferably the impregnation liquid also includes: 0.1-1wt% of a dispersant and 0.05-0.2wt% of a stabilizer; preferably, the surfactant is selected from any one or more of polyoxyethylene alkylphenol ethers, fatty alcohol polyoxyethylene ethers, and polyoxyethylene polyoxypropylene block esters, and the dispersant is preferably a fluorinated anionic surfactant; preferably, the fluorinated anionic surfactant is selected from any one or more of ammonium perfluorooctanoate, sodium perfluorooctanoate, potassium perfluorobutyl sulfonate, potassium perfluorohexyl sulfonate, and potassium perfluorooctane sulfonate; preferably, the stabilizer is solid paraffin, wherein the foaming agent is an alkyl glycoside, and preferably, the alkyl group in the alkyl glycoside is C8-C 16 The alkyl group is further preferably decyl glucoside.
[0009] Furthermore, the preparation process of the impregnation liquid comprises: stirring and mixing PTFE particles, a foaming agent and water to obtain an impregnation liquid; preferably, the stirring and mixing speed is 400 to 600 r / min, and the stirring and mixing time is preferably 10 to 30 min.
[0010] Furthermore, in the above step S2, the first impregnation process includes: stirring the PTFE needle felt in the catalyst dispersion for 5 to 10 minutes, and then ultrasonicating for 10 to 20 minutes, preferably the stirring speed is 400 to 800 r / min, and the ultrasonic frequency is preferably 28000 to 40000 Hz.
[0011] Furthermore, the preparation method also includes a process of hot pressing and drying the filter material after the second impregnation before calcination. The preferred hot pressing conditions are a pressure of 0.5 to 1 MPa, a hot pressing temperature of 80 to 100°C, a hot pressing time of 15 to 30 seconds, and a preferred drying temperature of 50 to 80°C.
[0012] According to another aspect of the present invention, there is provided a PTFE catalytic filter material prepared by the aforementioned preparation method.
[0013] Furthermore, the amount of catalyst attached to the PTFE needle felt per square meter is greater than 200 g / m 2 .
[0014] Furthermore, the PTFE catalytic filter material is repeatedly sprayed 400 to 500 times at a spray pressure of 0.2 MPa, and the catalyst powder loss rate is less than 10%. Preferably, the PTFE catalytic filter material is repeatedly sprayed 400 to 500 times at a spray pressure of 0.2 MPa, and the catalyst powder loss rate is less than 3%.
[0015] By applying the technical solution of the present invention, the PTFE needle felt has excellent heat resistance, corrosion resistance, and liquid resistance. The breaking strength of the base cloth will not decay after long-term use, and the service life is long. It is the preferred filter material for flue gas dust removal. The above method realizes the effective compounding of the denitration catalyst and the PTFE filter material, saving the device cost. Specifically, the above first impregnation makes the catalyst dispersion liquid evenly dispersed on the PTFE needle felt, and the second impregnation evenly disperses the nano-scale PTFE particles on the surface of the first impregnated filter material through the emulsification effect of the surfactant, thereby improving the firmness of the catalyst powder attached to the PTFE needle felt. At the same time, the nano-scale PTFE particles as the effective components of the impregnation liquid will not wrap or seal the nano-scale catalyst powder, and will not limit the penetration of the gas, ensuring a better contact reaction between the catalyst and the nitrogen oxides, and thus not affecting the high catalytic performance of the catalyst. Furthermore, the amount of catalyst attachment can be regulated by changing the number of impregnations. It is a method for preparing catalytic filter materials with high efficiency, controllable load, and simple and easy operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The SEM image of a PTFE catalytic filter material provided in Example 1 of the present invention at a magnification of 200 μm is shown;
[0018] Figure 2 Shows Figure 1 SEM image of the PTFE catalytic filter material shown at 2 μm magnification. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] As analyzed in the background technology, the prior art PTFE catalytic filter material has the problems of complex preparation process, large amount of catalyst used and poor catalytic effect. To solve this technical problem, the present invention provides a PTFE catalytic filter material and a preparation method thereof.
[0021] In a typical embodiment of the present application, a method for preparing a PTFE catalytic filter material is provided, and the preparation method comprises: step S1, mixing a catalyst with a solvent to obtain a catalyst dispersion; step S2, performing a first impregnation of the PTFE needle felt in the catalyst dispersion to obtain a first impregnated filter material; step S3, performing a second impregnation of the first impregnated filter material in the impregnation liquid to obtain a PTFE catalytic filter material, wherein the impregnation liquid comprises nano-scale PTFE particles and the particle size of the catalyst is nano-scale.
[0022] PTFE needle felt has excellent heat resistance, corrosion resistance, and liquid resistance. The breaking strength of the base cloth will not decay after long-term use, and the service life is long. It is the preferred filter material for flue gas dust removal. The above method can achieve effective compounding of denitration catalyst and PTFE filter material, saving the cost of the device. Specifically, the above first impregnation makes the catalyst dispersion evenly dispersed on the PTFE needle felt, and the second impregnation evenly disperses the nano-scale PTFE particles on the surface of the first impregnated filter material through the emulsification effect of the surfactant, thereby improving the firmness of the catalyst powder attached to the PTFE needle felt. At the same time, the nano-scale PTFE particles as the effective component of the impregnation liquid will not wrap or seal the nano-scale catalyst powder, and will not limit the penetration of the gas, ensuring a better contact reaction between the catalyst and nitrogen oxides, and thus not affecting the high catalytic performance of the catalyst. Furthermore, the amount of catalyst attachment can be regulated by changing the number of impregnations. It is an efficient, load-controllable, simple and easy-to-operate method for preparing catalytic filter materials.
[0023] In one embodiment of the present application, the above-mentioned preparation method also includes calcining the filter material after the second impregnation to obtain a PTFE catalytic filter material, wherein the PTFE needle-punched felt is a flat strip fiber, and the fiber fineness of the flat strip fiber is preferably 2 to 10 dtex, the particle size of the nano-scale PTFE particles is preferably 150 to 170 nm, the calcination temperature is preferably 250 to 270°C, and the calcination time is preferably 1 h to 2 h.
[0024] Under the above-mentioned calcination temperature conditions, the PTFE needle felt softens to a lower degree, but the flat strip fibers hardly deform significantly, and the PTFE particles softened by heat during the above-mentioned calcination process will have greater fluidity due to their small particles, thereby making the PTFE particles and the PTFE needle felt stably fused on the one hand, and forming a certain mesh structure between the PTFE particles on the other hand. The mesh structure improves the firmness of the catalyst powder attached to the PTFE needle felt on the one hand, and reduces the powder drop rate of the catalyst powder. On the other hand, the mesh structure will not wrap or seal the nano-scale catalyst powder, and will not limit the penetration of the gas (nitrogen oxides), ensuring a better contact reaction between the catalyst and the gas, and thus not affecting the high catalytic performance of the catalyst. And after the catalyst component is heated, it can not only desorb part of the solvent and gas remaining on the PTFE needle felt, but also promote the activation of the catalyst to generate active oxides, which is further conducive to improving the catalytic activity of the catalyst.
[0025] In order to obtain a more uniform catalyst dispersion, which is helpful for the subsequent attachment of the catalyst to the PTFE needle felt, the above mixing process preferably includes: stirring the catalyst and the solvent and then ultrasonicating, preferably the stirring speed is 400-800r / min, preferably the stirring time is 5-10 minutes; preferably the ultrasonic frequency is 28000-40000Hz, preferably the ultrasonic time is 10-20 minutes, preferably the volume ratio of the catalyst to the solvent is 1:5-15, preferably the particle size of the catalyst is 30-58nm, and the catalyst is preferably selected from 3wt% Any one or more of V2O5-10wt%MoO3 / TiO2 catalyst, 3wt%V2O5-10wt%MoO3-xwt%CeO2 / TiO2, 3wt%V2O5-10wt%WO3 / TiO2, wherein x ranges from 1 to 10, and the mass percentage of each component in the catalyst is relative to the mass of TiO2 in the catalyst as 100%; the preferred solvent is any one or more of ethanol, propanol, acetone, and a mixed solution of ethanol and water, wherein the water content in the mixed solution is ≤13%. In addition, if the particle size of the catalyst is too large, it is easy to settle, which is not conducive to the dispersion and attachment of the catalyst. If the particle size of the catalyst is too small, it is easy to cause agglomeration between the catalyst powders, which is not conducive to the stability and control of its particle size. The catalyst and type of the above-mentioned particle size are preferred to help improve the catalytic effect of the PTFE catalytic filter material.
[0026] In one embodiment of the present application, in the above step S3, the second impregnation is repeated multiple times, and preferably the process of each second impregnation includes: after impregnating the front side of the first impregnated filter material for 5 to 10 minutes, turning the first impregnated filter material over and then impregnating it for 5 to 10 minutes; preferably, the second impregnation is repeated 2 to 3 times, and preferably, in terms of mass percentage, the impregnation liquid includes: 0.3 to 12 wt% of PTFE particles; 0.05 to 1.5 wt% of the surfactant; 0.1 to 5 wt% of the foaming agent and 83 to 99.6 wt% of water, preferably the impregnation liquid The invention also comprises: 0.1-1 wt% of a dispersant and 0.05-0.2 wt% of a stabilizer; preferably, the surfactant is selected from any one or more of polyoxyethylene alkylphenol ether, fatty alcohol polyoxyethylene ether, and polyoxyethylene polyoxypropylene block ester, and the dispersant is preferably a fluorine-containing anionic surfactant; preferably, the fluorine-containing anionic surfactant is selected from any one or more of ammonium perfluorooctanoate, sodium perfluorooctanoate, potassium perfluorobutyl sulfonate, potassium perfluorohexyl sulfonate, and potassium perfluorooctane sulfonate; preferably, the stabilizer is solid paraffin, wherein the foaming agent is an alkyl glycoside, and preferably, the alkyl group in the alkyl glycoside is C8-C 16 The alkyl group is further preferably decyl glucoside.
[0027] The foaming agent and stirring and mixing make the PTFE particles dispersed more evenly in the impregnation liquid. The PTFE particles with the above particle size are more conducive to the penetration of gas while fixing the catalyst on the PTFE needle felt, ensuring a better contact reaction between the catalyst and nitrogen oxides, thereby not affecting the high catalytic performance of the catalyst. By controlling the number of the first impregnation, a high-efficiency PTFE catalytic filter material with controllable loading can be obtained. Preferably, the above first impregnation number can obtain a PTFE catalytic filter material with a high catalyst loading.
[0028] Preferably, the preparation process of the above-mentioned impregnation liquid includes: stirring and mixing PTFE particles, foaming agent and water to obtain an impregnation liquid; preferably, the stirring and mixing speed is 400-600r / min, and the stirring and mixing time is preferably 10-30min, so that the obtained impregnation liquid is more uniform.
[0029] In one embodiment of the present application, in the above step S2, the first impregnation process includes: stirring the PTFE needle felt in the catalyst dispersion for 5 to 10 minutes, and then ultrasonicating for 10 to 20 minutes. The preferred stirring speed is 400 to 800 r / min, and the preferred ultrasonic frequency is 28000 to 40000 Hz.
[0030] The catalyst dispersion is more evenly distributed around the PTFE needle-punched felt by stirring, and the catalyst dispersion is dispersed into smaller and more even droplets by ultrasound, thereby helping the catalyst in the catalyst dispersion to adhere to the PTFE needle-punched felt.
[0031] In order to further attach the catalyst more firmly to the PTFE needled felt, the above preparation method preferably also includes a process of hot pressing and drying the filter material after the second impregnation before calcination. The preferred hot pressing conditions are a pressure of 0.5 to 1 MPa, a hot pressing temperature of 80 to 100° C., a hot pressing time of 15 to 30 seconds, and a preferred drying temperature of 50 to 80° C.
[0032] In another typical embodiment of the present application, a PTFE catalytic filter material is provided. The PTFE catalytic filter material is prepared by the aforementioned preparation method.
[0033] The above PTFE catalytic filter material of the present application enables the catalyst to be firmly attached to the PTFE needle-punched felt through the emulsification and bonding effect of the PTFE particles, wherein the PTFE particles will not wrap or seal the catalyst powder and will not restrict the penetration of the gas, thereby ensuring a better contact reaction between the catalyst and nitrogen oxides, thereby ensuring the high catalytic performance of the catalyst, thereby not only overcoming the problem in the prior art that the catalyst is not easy to adhere to the substrate and is easy to fall off, but also using less catalyst can achieve excellent catalytic effect, greatly reducing the cost.
[0034] In one embodiment of the present application, the amount of catalyst attached to the PTFE needle felt per square meter is greater than 200 g / m 2 , the preferred catalyst particle size is 30 to 58 nm.
[0035] The amount of catalyst attached to the PTFE needle-punched felt per square meter is beneficial to improving the catalytic effect of the PTFE catalytic filter material per unit square meter.
[0036] Preferably, the PTFE catalytic filter material is repeatedly sprayed 400 to 500 times at a spraying pressure of 0.2 MPa, and the catalyst powder loss rate is lower than 10%. Preferably, the PTFE catalytic filter material is repeatedly sprayed 400 to 500 times at a spraying pressure of 0.2 MPa, and the catalyst powder loss rate is lower than 3%. Further selecting a PTFE catalytic filter material with a strong catalyst attachment is beneficial to ensuring its excellent catalytic effect.
[0037] The beneficial effects of the present application will be described below in conjunction with specific embodiments.
[0038] Example 1
[0039] According to the mass fraction of each component in the 3wt% V2O5-10wt% MoO3 / TiO2 catalyst composition, the addition amount of the active component precursor ammonium metavanadate, the auxiliary agent precursor ammonium molybdate and nano-grade rutile TiO2 is calculated, dissolved in oxalic acid solution and stirred for 30 minutes to make it completely dissolved, the prepared solution is dried in a 100°C oven for 12 hours, and calcined in a 350°C muffle furnace for 5 hours. After cooling, the denitrification and de-evil removal catalyst can be obtained. The catalyst is ground into powder and sieved to obtain 100 mesh 3wt% V2O5-10wt% MoO3 / TiO2 catalyst powder.
[0040] 1.81wt% of PTFE particles (using 60wt% PTFE emulsion, model P816262 (Shanghai McLean Biochemical Technology Co., Ltd.), the average particle size of the PTFE particles is 160nm), 0.22wt% of decyl glucoside (APG0810), 0.05% of polyoxyethylene alkylphenol ether surfactant (Shanghai McLean Biochemical Technology Co., Ltd.), 0.1% of sodium perfluorooctanoate dispersant (Shanghai McLean Biochemical Technology Co., Ltd.), 0.05% of solid paraffin stabilizer (Shanghai McLean Biochemical Technology Co., Ltd.) and 97.77wt% of water are stirred at room temperature at a speed of 500r / min for 20 minutes to obtain an impregnation solution.
[0041] Weigh 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder and dissolve it in 60 mL of ethanol. Stir for 10 minutes and ultrasonicate at a frequency of 28,000 Hz for 10 minutes to form a catalyst dispersion.
[0042] A PTFE filter material with a diameter of 10 cm (model: pure PTFE needle felt, fiber fineness: 8 dtex) was immersed in the catalyst dispersion, stirred at a speed of 600 r / min at room temperature for 10 minutes, ultrasonicated at a frequency of 28000 Hz for 20 minutes to form a first impregnated filter material, and dried at 80°C.
[0043] The first impregnated filter material is immersed in the impregnation liquid, immersed on the front side for 6 minutes, then turned over and immersed for another 6 minutes, and hot-pressed at a pressure of 1 MPa, a temperature of 100°C, and a time of 15 seconds, and then placed in an oven at 80°C for drying; the dried catalytic filter material is calcined in a muffle furnace at 260°C for 2 hours to obtain a PTFE catalytic filter material.
[0044] Example 2
[0045] The difference from Example 1 is that 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder is dissolved in 120 mL of ethanol to form a catalyst dispersion, and finally a PTFE catalytic filter material is obtained.
[0046] Example 3
[0047] The difference from Example 1 is that 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder is dissolved in 180 mL of ethanol to form a catalyst dispersion, and finally a PTFE catalytic filter material is obtained.
[0048] Example 4
[0049] The difference from Example 1 is that 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder is dissolved in 500 mL of ethanol to form a catalyst dispersion, and finally a PTFE catalytic filter material is obtained.
[0050] Example 5
[0051] The difference from Example 1 is that the calcination temperature is 250° C., and a PTFE catalytic filter material is finally obtained.
[0052] Example 6
[0053] The difference from Example 1 is that the calcination temperature is 270° C., and a PTFE catalytic filter material is finally obtained.
[0054] Example 7
[0055] The difference from Example 1 is that the dried catalytic filter material is not calcined, and the dried catalytic filter material is directly used as the final PTFE catalytic filter material.
[0056] Example 8
[0057] The difference from Example 1 is that 0.3wt% of PTFE particles, 0.1wt% of alkyl glycoside, 0.05% of polyoxyethylene alkylphenol ether surfactant, 0.1% of sodium perfluorooctanoate dispersant, 0.05% of solid paraffin stabilizer and 99.4wt% of water are stirred at room temperature at a speed of 500r / min for 20 minutes to obtain an impregnation solution, and finally a PTFE catalytic filter material is obtained.
[0058] Example 9
[0059] The difference from Example 1 is that 12wt% of PTFE particles, 5wt% of alkyl glycoside, 0.05% of polyoxyethylene alkylphenol ether surfactant, 0.1% of sodium perfluorooctanoate dispersant, 0.05% of solid paraffin stabilizer and 82.8wt% of water are stirred at room temperature at a speed of 500r / min for 20 minutes to obtain an impregnation solution, and finally a PTFE catalytic filter material is obtained.
[0060] Example 10
[0061] The difference from Example 1 is that 0.2wt% of PTFE particles, 6wt% of alkyl glycoside, 0.05% of polyoxyethylene alkylphenol ether surfactant, 0.1% of sodium perfluorooctanoate dispersant, 0.05% of solid paraffin stabilizer and 93.6wt% of water are stirred at room temperature at a speed of 500r / min for 20 minutes to obtain an impregnation solution, and finally a PTFE catalytic filter material is obtained.
[0062] Embodiment 11
[0063] The difference from Example 1 is that the PTFE filter material is immersed in the catalyst dispersion, stirred at a speed of 600 r / min at room temperature for 10 minutes, and no ultrasound is performed to form a first impregnated filter material, and finally a PTFE catalytic filter material is obtained.
[0064] Example 12
[0065] The difference from Example 1 is that 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder is weighed and dissolved in 60 mL of a mixture of ethanol and water (the volume ratio of ethanol to water is 87:13) to form a catalyst dispersion, and finally a PTFE catalytic filter material is obtained.
[0066] Embodiment 13
[0067] The difference from Example 1 is that 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder is weighed and dissolved in 60 mL of a mixture of ethanol and water (the volume ratio of ethanol to water is 80:20) to form a catalyst dispersion, and finally a PTFE catalytic filter material is obtained.
[0068] Embodiment 14
[0069] The difference from Example 1 is that the first impregnation is repeated three times to finally obtain the PTFE catalytic filter material.
[0070] Embodiment 15
[0071] The difference from Example 1 is that the catalyst is 3wt% V2O5-10wt% MoO3-5wt% CeO2 / TiO2, and PTFE catalytic filter material is finally obtained.
[0072] Example 16
[0073] The difference from Example 1 is that the catalyst is 3wt% V2O5-10wt% WO3 / TiO2, and PTFE catalytic filter material is finally obtained.
[0074] Embodiment 17
[0075] According to the mass fraction of each component in the 3wt% V2O5-10wt% MoO3 / TiO2 catalyst composition, the addition amount of the active component precursor ammonium metavanadate, the auxiliary agent precursor ammonium molybdate and nano-grade rutile TiO2 is calculated, dissolved in oxalic acid solution and stirred for 30 minutes to make it completely dissolved, the prepared solution is dried in a 100°C oven for 12 hours, and calcined in a 350°C muffle furnace for 5 hours. After cooling, the denitrification and de-evil removal catalyst is obtained, the catalyst is ground into powder, and sieved to obtain 500 mesh 3wt% V2O5-10wt% MoO3 / TiO2 catalyst powder.
[0076] 1.81wt% of PTFE particles (using 60wt% PTFE emulsion, model P816262 (Shanghai McLean Biochemical Technology Co., Ltd.), the average particle size of the PTFE particles is 170nm), 0.22wt% of decyl glucoside (APG0810), 0.05% of polyoxyethylene alkylphenol ether surfactant (Shanghai McLean Biochemical Technology Co., Ltd.), 0.1% of sodium perfluorooctanoate dispersant (Shanghai McLean Biochemical Technology Co., Ltd.), 0.05% of solid paraffin stabilizer (Shanghai McLean Biochemical Technology Co., Ltd.) and 97.77wt% of water are stirred at room temperature at a speed of 600r / min for 30 minutes to obtain an impregnation solution.
[0077] Weigh 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder and dissolve it in 60 mL of ethanol. Stir it at 300 r / min at room temperature for 10 minutes and ultrasonicate it at a frequency of 28000 Hz for 20 minutes to form a catalyst dispersion.
[0078] A PTFE filter material with a diameter of 10 cm (model: pure PTFE needle felt, fiber fineness: 2 dtex) was immersed in the catalyst dispersion, stirred at 300 r / min for 10 minutes at room temperature, ultrasonicated at a frequency of 40,000 Hz for 20 minutes to form a first impregnated filter material, and dried at 80°C.
[0079] The first impregnated filter material was immersed in the impregnation liquid, immersed on the front side for 6 minutes, then turned over and immersed again for 6 minutes, and hot-pressed at a pressure of 0.5 MPa, a temperature of 80°C, and a time of 30 seconds, and then placed in an oven at 80°C for drying; the dried catalytic filter material was calcined in a muffle furnace at 260°C for 2 hours to obtain a PTFE catalytic filter material.
[0080] Comparative Example 1
[0081] The difference from Example 1 is that the filter material substrate is basalt fiber.
[0082] Weigh 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder and dissolve it in 60 mL of ethanol. Stir for 10 minutes and ultrasonicate at a frequency of 28,000 Hz for 10 minutes to form a catalyst dispersion.
[0083] A basalt fiber filter material with a diameter of 10 cm was immersed in the catalyst dispersion, stirred at a speed of 600 r / min at room temperature for 10 minutes, ultrasonicated at a frequency of 28000 Hz for 20 minutes to form a first impregnated filter material, and dried at 80°C.
[0084] The first impregnated filter material was immersed in the PTFE impregnation solution, immersed on the front side for 6 minutes, then turned over and immersed again for 6 minutes, and then hot-pressed at a pressure of 1 MPa, a temperature of 100°C, and a time of 15 seconds, and then placed in an oven at 80°C for drying; the dried catalytic filter material was calcined in a muffle furnace at 260°C for 2 hours to obtain a basalt fiber catalytic filter material.
[0085] Comparative Example 2
[0086] The difference from Example 1 is that the first impregnated filter material is directly hot-pressed at a pressure of 1 MPa, a temperature of 100°C, and a time of 15 s and then placed in an oven at 80°C for drying without a second impregnation; the dried catalytic filter material is calcined in a muffle furnace at 260°C for 2 hours to obtain a PTFE catalytic filter material.
[0087] Comparative Example 3
[0088] The difference from Example 1 is that the first impregnated filter material is immersed in the silica sol impregnation liquid (10% silica sol solution), immersed on the front side for 6 minutes and then turned over and immersed again for 6 minutes, and then hot-pressed at a pressure of 1 MPa, a temperature of 100°C, and a time of 15 seconds and then placed in an oven at 80°C for drying; the dried catalytic filter material is calcined in a muffle furnace at 260°C for 2 hours to obtain a PTFE catalytic filter material.
[0089] Comparative Example 4
[0090] The difference from Example 1 is that the substrate is polyimide (P84).
[0091] Weigh 10 g of 3 wt% V2O5-10 wt% MoO3 / TiO2 powder and dissolve it in 60 mL of ethanol. Stir for 10 minutes and ultrasonicate at a frequency of 28,000 Hz for 10 minutes to form a catalyst dispersion.
[0092] A polyimide filter material with a diameter of 10 cm was immersed in the catalyst dispersion, stirred at a speed of 600 r / min at room temperature for 10 minutes, ultrasonicated at a frequency of 28000 Hz for 20 minutes to form a first impregnated filter material, and dried at 80°C.
[0093] The first impregnated filter material is immersed in the impregnation liquid, immersed on the front side for 6 minutes, then turned over and immersed for another 6 minutes, and hot-pressed at a pressure of 1 MPa, a temperature of 100° C., and a time of 15 seconds, and then placed in an oven at 80° C. for drying; the dried catalytic filter material is calcined in a muffle furnace at 260° C. for 2 hours to obtain a polyimide catalytic filter material.
[0094] The amount of catalyst attached to each PTFE catalytic filter material in the above-mentioned Examples 1 to 17 and Comparative Examples 1 to 4 was repeatedly sprayed 400 to 500 times at a spraying pressure of 0.2 MPa, and the amount of catalyst attached and the catalyst powder loss rate were listed in Table 1.
[0095] The denitrification performance of the PTFE catalytic filter material was tested under the conditions of 230°C, a gas velocity of 0.8 m / min, a NO content of 500 ppm, a NH3 content of 600 ppm, and 8% O2, and the denitrification rates are listed in Table 1.
[0096] Table 1
[0097]
[0098]
[0099] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0100] PTFE needle felt has excellent heat resistance, corrosion resistance, and liquid resistance. The breaking strength of the base cloth will not decay after long-term use, and the service life is long. It is the preferred filter material for flue gas dust removal. The above method can achieve effective compounding of denitration catalyst and PTFE filter material, saving the cost of the device. Specifically, the above first impregnation makes the catalyst dispersion evenly dispersed on the PTFE needle felt, and the second impregnation evenly disperses the nano-scale PTFE particles on the surface of the first impregnated filter material through the emulsification effect of the surfactant, thereby improving the firmness of the catalyst powder attached to the PTFE needle felt. At the same time, the nano-scale PTFE particles as the effective component of the impregnation liquid will not wrap or seal the nano-scale catalyst powder, and will not limit the penetration of the gas, ensuring a better contact reaction between the catalyst and nitrogen oxides, and thus not affecting the high catalytic performance of the catalyst. Furthermore, the amount of catalyst attachment can be regulated by changing the number of impregnations. It is an efficient, load-controllable, simple and easy-to-operate method for preparing catalytic filter materials.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a PTFE catalytic filter material, characterized in that: The preparation method comprises: Step S1, mixing the catalyst and the solvent to obtain a catalyst dispersion; Step S2, performing a first impregnation of the PTFE needle-punched felt in the catalyst dispersion to obtain a first impregnated filter material; Step S3, performing a second impregnation on the first impregnated filter material in an impregnation liquid to obtain a PTFE catalytic filter material, Wherein, the impregnation liquid comprises nano-scale PTFE particles and a surfactant, and the particle size of the catalyst is nano-scale; The second impregnated filter material is calcined to obtain the PTFE catalytic filter material. The calcination temperature is 250-270°C; The particle size of the catalyst is 30-58 nm, and the catalyst is selected from 3wt% V2O5-10wt% MoO3 / TiO2 catalyst, 3wt% V2O5-10wt% MoO3- x Any one or more of wt%CeO2 / TiO2, 3wt%V2O5-10wt%WO3 / TiO2, wherein, x The range is 1 to 10, and the mass percentage of each component in the catalyst is relative to the mass of TiO2 in the catalyst as 100%; The second dipping is repeated multiple times, and the process of each second dipping includes: After the front side of the first impregnated filter material is impregnated for 5 to 10 minutes, the first impregnated filter material is turned over and impregnated for another 5 to 10 minutes; In terms of mass percentage, the impregnation solution comprises: 0.3-12wt% of the PTFE particles; 0.05-1.5wt% of the surfactant; 0.1~5wt% of a blowing agent; and 83~99.6wt% water; The surfactant is selected from any one or more of polyoxyethylene alkylphenol ethers, fatty alcohol polyoxyethylene ethers, and polyoxyethylene polyoxypropylene block esters.
2. The preparation method according to claim 1, characterized in that: The preparation method also includes: the PTFE needle-punched felt is a flat strip-shaped fiber.
3. The preparation method according to claim 2, characterized in that: The fiber fineness of the flat strip fibers is 2-10 dtex.
4. The preparation method according to claim 1, characterized in that: The particle size of the nano-scale PTFE particles is 150-170 nm.
5. The preparation method according to claim 1, characterized in that: The calcination time is 1h~2h.
6. The preparation method according to any one of claims 1 to 5, characterized in that In step S1, the mixing process includes: The catalyst and the solvent are mixed and stirred first and then ultrasonicated, and the stirring speed is 400-800 r / min.
7. The preparation method according to claim 6, characterized in that: The stirring time is 5 to 10 minutes.
8. The preparation method according to claim 6, characterized in that: The frequency of the ultrasound is 28000~40000 Hz.
9. The preparation method according to claim 6, characterized in that: The ultrasonic time is 10 to 20 minutes.
10. The preparation method according to claim 6, characterized in that: The volume ratio of the catalyst to the solvent is 1:5-15.
11. The preparation method according to claim 6, characterized in that: The solvent is selected from any one or more of ethanol, propanol, acetone, and a mixed solution of ethanol and water, wherein the content of water in the mixed solution is ≤13%.
12. The preparation method according to any one of claims 1 to 5, characterized in that: In the step S3, the first dipping is repeated 2 to 3 times.
13. The preparation method according to any one of claims 1 to 5, characterized in that: The impregnation solution also includes: 0.1-1 wt % of a dispersant and 0.05-0.2 wt % of a stabilizer.
14. The preparation method according to claim 13, characterized in that: The dispersant is a fluorine-containing anionic surfactant.
15. The preparation method according to claim 14, characterized in that: The fluorine-containing anionic surfactant is selected from any one or more of ammonium perfluorooctanoate, sodium perfluorooctanoate, potassium perfluorobutylsulfonate, potassium perfluorohexylsulfonate, and potassium perfluorooctanesulfonate.
16. The preparation method according to claim 13, characterized in that: The stabilizer is solid paraffin.
17. The preparation method according to any one of claims 1 to 5, characterized in that: The foaming agent is alkyl glycoside.
18. The preparation method according to claim 17, characterized in that: The alkyl group in the alkyl glycoside is C8~C 16 of alkyl.
19. The preparation method according to claim 18, characterized in that: The foaming agent is decyl glucoside.
20. The preparation method according to claim 1, characterized in that: The preparation process of the impregnation solution comprises: The PTFE particles, the foaming agent and the water are stirred and mixed to obtain the impregnation liquid.
21. The preparation method according to claim 20, characterized in that: The stirring and mixing speed is 400-600 r / min.
22. The preparation method according to claim 20, characterized in that: The stirring and mixing time is 10 to 30 minutes.
23. The preparation method according to claim 1, characterized in that: In step S2, the first impregnation process includes: The PTFE needle felt is first stirred in the catalyst dispersion for 5 to 10 minutes, and then ultrasonicated for 10 to 20 minutes.
24. The preparation method according to claim 23, characterized in that: The stirring speed is 400-800 r / min.
25. The preparation method according to claim 23, characterized in that: The frequency of the ultrasound is 28000~40000 Hz.
26. The preparation method according to claim 1, characterized in that: The preparation method further comprises the process of hot pressing and drying the second impregnated filter material before the calcination.
27. The preparation method according to claim 26, characterized in that: The hot pressing conditions are as follows: a pressure of 0.5-1 MPa, a hot pressing temperature of 80-100° C., and a hot pressing time of 15-30 seconds.
28. The preparation method according to claim 26, characterized in that: The drying temperature is 50-80°C.
29. A PTFE catalytic filter material, characterized in that: The PTFE catalytic filter material is prepared by the preparation method described in any one of claims 1 to 28.
30. The PTFE catalytic filter material according to claim 29, characterized in that: The amount of catalyst attached to the PTFE needle felt per square meter is > 200 g / m 2 .
31. The PTFE catalytic filter material according to claim 30, characterized in that: The PTFE catalytic filter material is repeatedly sprayed 400 to 500 times at a spraying pressure of 0.2 MPa, and the powder loss rate of the catalyst is less than 10%.
32. The PTFE catalytic filter material according to claim 31, characterized in that: The PTFE catalytic filter material was repeatedly sprayed 400 to 500 times at a spraying pressure of 0.2 MPa, and the powder loss rate of the catalyst was less than 3%.
Citation Information
Patent Citations
Polytetrafluoroethylene glass fiber breathable varnished cloth and formula
CN104532578A
Preparation method of filter cloth loaded vanadium titanium based catalytic denitration material
CN109759053A
Waterproof high-wear-resistance PTFE filter material and preparation method thereof
CN114130120A